Vitamin C-Dependent Uptake of Non-Heme Iron by Enterocytes, Its Impact on Erythropoiesis and Redox Capacity of Human Erythrocytes - Xia Pan; Martin Köberle; Mehrdad Ghashghaeinia (MDPI AG, 2024)
In the small intestine, nutrients from ingested food are absorbed and broken down by enterocytes, which constitute over 95% of the intestinal epithelium. Enterocytes demonstrate diet- and segment-dependent metabolic flexibility, enabling them to take up large amounts of glutamine and glucose to meet their energy needs and transfer these nutrients into the bloodstream. During glycolysis, ATP, lactate, and H+ ions are produced within the enterocytes. Based on extensive but incomplete glutamine oxidation large amounts of alanine or lactate are produced. Lactate, in turn, promotes hypoxia-inducible factor-1α (Hif-1α) activation and Hif-1α-dependent transcription of various proton channels and exchangers, which extrude cytoplasmic H+-ions into the intestinal lumen. In parallel, the vitamin C-dependent and duodenal cytochrome b-mediated conversion of ferric iron into ferrous iron progresses. Finally, the generated electrochemical gradient is utilized by the divalent metal transporter 1 for H+-coupled uptake of non-heme Fe2+-ions. Iron efflux from enterocytes, subsequent binding to the plasma protein transferrin, and systemic distribution supply a wide range of cells with iron, including erythroid precursors essential for erythropoiesis. In this review, we discuss the impact of vitamin C on the redox capacity of human erythrocytes and connect enterocyte function with iron metabolism, highlighting its effects on erythropoiesis.